SPE/IATMI Asia Pacific Oil &Amp; Gas Conference and Exhibition 2017
DOI: 10.2118/186976-ms
|View full text |Cite
|
Sign up to set email alerts
|

200 and Counting: Unlocking CBM Potential with High-Strength, Low-Density Cement Slurry

Abstract: During primary cementing of coalbed methane (CBM) wells, it is necessary to consider slurry designs not typically encountered during conventional cementing operations. An important difference between coal seams and conventional reservoirs is the cleat system of coal. This unique petrophysical property of coal should be factored into the design to meet the basic tenets of primary cementing (i.e., zonal isolation and casing support). This paper presents cement design considerations, case histories, and best prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Foamed cement has higher resistance to cyclic stresses of temperature and pressure expected downhole. This is because of the low Young’s modulus and high Poisson’s ratio of this system compared to cement systems made with conventional materials.…”
Section: Properties Of Foamed Cement Slurry and The Generated Sheathmentioning
confidence: 99%
See 2 more Smart Citations
“…Foamed cement has higher resistance to cyclic stresses of temperature and pressure expected downhole. This is because of the low Young’s modulus and high Poisson’s ratio of this system compared to cement systems made with conventional materials.…”
Section: Properties Of Foamed Cement Slurry and The Generated Sheathmentioning
confidence: 99%
“…Nowadays, several oil wells have been drilled through weak formations or targeting weak hydrocarbon bearing formations such as coal bed methane (CBM) reservoirs. CBM reservoirs are associated with weak and less stable formations with low fracture pressure. The use of conventional cement, which is brittle, usually fails in primary jobs under the annular deformation and cyclic stress loads associated with CBM formations. Foam cement, which is more elastic, improved the cement sheath stability under the annular deformation across the CBM formations and increased the possibility of success for the primary cementing job. Fidan et al reported successful field application of foam cement in CBM reservoirs in several wells in Western Canada.…”
Section: Field Applications Of the Foam Cement In Oil Industrymentioning
confidence: 99%
See 1 more Smart Citation